Clinical and pathological analysis of indolent T-cell lymphoproliferative disease of the gastrointestinal tract - Yuan, Dan; Liang, Na; Wang, Dong-Yue; Wang, Jin-Jing; Jia, Cong-Wei (Frontiers in Immunology, 2025)
ObjectiveThis study aimed to investigate the clinicopathological features of indolent T-cell lymphoproliferative disease of the gastrointestinal tract (ITLPD-GI) and to improve its diagnostic and therapeutic approaches.MethodsA retrospective analysis was conducted on eight ITLPD-GI patients treated between January 2018 and January 2024. Clinical data, pathological features, immunophenotypes, molecular testing results, and follow-up records were reviewed.ResultsClinical characteristics: Male-to-female ratio 3:5; mean age at onset 42 years. Symptoms: Predominantly diarrhea and abdominal pain. Endoscopic findings: Erosions, multiple shallow ulcers, and small polypoid lesions. Pathological features: Histology: Atrophy of gastric/intestinal glands with diffuse infiltration of small lymphocytes (round/irregular nuclei, dense chromatin) in the lamina propria; rare mitoses; absence of angioinvasion or necrosis. Notably, two cases showed prominent plasma cell infiltration in the superficial mucosa. Immunophenotype: Pan-T-cell markers positive (5/8); CD4−/CD8+ (5/8), CD4+/CD8+ (2/8), CD4+/CD8− (1/8); aberrant CD20 expression (2/8); low Ki-67 index. TCR rearrangement: Monoclonal in all four tested cases. Treatment and prognosis: Supportive therapy (five cases): Dietary modification, immunosuppression, immunomodulation, and anti-infective agents. Symptoms resolved in one case but persisted in four. Targeted therapy (one CD20+ case): Rituximab added, with no improvement after 14 months of follow-up. Chemotherapy (two cases): Prednisone + thalidomide; one achieved significant remission at 9 months, while the other showed no response (persistent diarrhea/anxiety) at 35 months. No disease progression was observed during follow-up.ConclusionITLPD-GI is a rare indolent monoclonal T-cell proliferation with non-specific clinical/endoscopic features, necessitating differentiation from aggressive lymphomas to avoid misdiagnosis and overtreatment. Diagnosis relies on histomorphology, immunohistochemistry, and TCR clonality assessment (critical for atypical cases, e.g., CD20+). The majority of patients have favorable outcomes with conservative management. Enhanced clinical awareness and novel therapeutic targets warrant further exploration.